Mudanças funcionais e cognitivas em idosos no município de Belo Horizonte: estudo longitudinal - Carolina de Senna Figueiredo (2012)
The aging process associated to the amplification of life expectancy of the population may result in an increase of the prevalence and incidence of diseases and loss of functionality. Physical dependency and cognition deficit may interfere in the performance of activities, engendering an overload of care to the family and the health system. The studies that associate cognition and functionality of elderly people, in Brazil, are rare and present predominantly a cross-sectional design. There is a necessity of longitudinal studies in which could be discussed the process of cognition changes and functional capacity. This study aims to compare the functional and cognitive changes in elderly people in the City of Belo Horizonte MG, occurred in a period of 06 months. It is a longitudinal observational study, with a sample of 167 elderly people, selected from a database of Rede de Estudos da Fragilidade em Idosos Brasileiros (Rede FIBRA) of UFMG. The functional capacity was assessed by Katz index, Lawton scale and a scale of Advanced Activity of Daily Life (AADL) developed by Rede FIBRA. The cognition was assessed by Mini-mental state examination (MMSE). It was observed a decrease in the functional capacities in Instrumental Activities of Daily Living (IADL), p=0,002, and Basic Activities of Daily Life (BADL), p=0,038, in some specific activities: Continence, Cooking and Housework. The variables Living alone (OR=2,53; IC=1,09:5,87) and working condition (OR=2,52; IC=1,18:5,41) have been associated to the changes in IADL. There was no significative difference when comparing both times for the scale of AADL (p=0,163) and MMSE (p=0,059). It was observed that the individual with better cognition were more independent in AADL and IADL. These results point to the necessity of interventions that aim the maintainability of the functionality. The relatives who live with elderly people must be oriented to encourage the independency and autonomy in the activities of daily living, enriching the capacities and potential of the elderly. Its important to invest in programs that encourage the social participation and enlargement of the network of contacts and insertion/support to the elderly in the labor market, performing whether in volunteers activities or not.